Habitat fragmentation and its implications for Endangered chimpanzee Pan troglodytes conservation. Issue 3 (20th July 2015) - Knight, Alexander; Chapman, Hazel M.; Hale, Marie
Abstract: Taraba State, Nigeria, is an important conservation site for the Endangered Nigeria–Cameroon chimpanzee Pan troglodytes ellioti . Gashaka Gumti National Park, Nigeria's largest national park and home to potentially the largest contiguous population of the Nigeria–Cameroon chimpanzee, spans a significant portion of the eastern sector of Taraba and the adjoining Adamawa State. South of the Park, Ngel Nyaki Forest Reserve comprises two forest fragments and holds a small population of chimpanzees. We investigated the existence of patterns in population structure and dispersal within this region, using microsatellite loci extracted from non-invasive sources of DNA. Our results indicate that dispersal and thus gene flow between the groups of chimpanzees at the Park and Reserve is limited, at least more so than it is within the Park, and we identified a biased sex ratio at the Reserve, forewarning of potential conservation concerns in relation to demographic and genetic stochasticity. We discuss conservation actions that may be applicable to sustaining the population within Ngel Nyaki Forest Reserve.